Penerapan Association Rule Untuk Menentukan Lama Studi Mahasiswa di Universitas Graha Nusantara Padangsidimpuan - Alwendi; Andi Saputra Mandopa (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
Very high information needs are sometimes not matched by providing adequate information, so that information must be extracted again in large data. By using the association rule technique, we can obtain information from large data such as data in universities. The purpose of this study was to determine the pattern of length of study of F-KIP students at Graha Nusantara University. by using the association rule data mining method and comparing the a priori algorithm and the hash-based algorithm. The data used is main data of F-KIP Graha Nusantara University which is processed using association rule data mining techniques with a priori algorithms and hash-based algorithms with a minimum support of 1% and a minimum trust of 1%. The results of data processing with the a priori algorithm are the same as the results of data processing with hash-based algorithms, namely 49 2-itemset combinations. The pattern that is formed is that 7.5% of graduates from the mathematics department study for more than 5 years with a confidence score of 38.5%.